2013
DOI: 10.1186/1471-2458-13-434
|View full text |Cite
|
Sign up to set email alerts
|

Dengue in peri-urban Pak-Ngum district, Vientiane capital of Laos: a community survey on knowledge, attitudes and practices

Abstract: BackgroundDengue remains an important cause of morbidity in Laos. Good knowledge, attitudes and practices (KAP) among the public regarding dengue prevention are required for the success of disease control. Very little is known about dengue KAP among the Lao general population.MethodsThis was a KAP household survey on dengue conducted in a peri-urban Pak-Ngum district of Vientiane capital, Laos. A two-stage cluster sampling method was used to select a sample of participants to represent the general community. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
64
5
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 12 publications
21
64
5
5
Order By: Relevance
“…Although DENV is transmitted by the bites of infected A. aegpyti and A. albopictus , only 19% of the respondents stated that Aedes mosquitoes transmit DENV and only 7% could identify such mosquitoes. In contrast to ours, a study from Laos showed that about 93% of the participants knew that A. aegypti was the specific mosquito species that transmits DENV [40]. More importantly, more than 56% of the participants in our study were not aware of the fact that ordinary person to person contact does not transmit DENV, highlighting the need for proper education about the protection from Aedes mosquito bites and the care of community members suffering from DF.…”
Section: Discussioncontrasting
confidence: 97%
“…Although DENV is transmitted by the bites of infected A. aegpyti and A. albopictus , only 19% of the respondents stated that Aedes mosquitoes transmit DENV and only 7% could identify such mosquitoes. In contrast to ours, a study from Laos showed that about 93% of the participants knew that A. aegypti was the specific mosquito species that transmits DENV [40]. More importantly, more than 56% of the participants in our study were not aware of the fact that ordinary person to person contact does not transmit DENV, highlighting the need for proper education about the protection from Aedes mosquito bites and the care of community members suffering from DF.…”
Section: Discussioncontrasting
confidence: 97%
“…However, many admitted to not paying much attention to government-produced commercials. This fact is not in line with other studies conducted with non-indigenous populations [22,29,30].…”
Section: Discussioncontrasting
confidence: 93%
“…There is insufficient proof to link knowledge as a determining factor for improving practices. [38] Further studies should assess the practices of participants towards Zika prevention.…”
Section: Discussionmentioning
confidence: 99%